2009
DOI: 10.4081/1211
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of constitutive and inducible Heat Shock Protein 70 in carp (Cyprinus carpio) and trout (Oncorhynchus mykiss) exposed to transport stress

Abstract: In the present work we investigated by immunohistochemistry the cellular localization of constitutive as well as inducible heat shock protein 70 in several tissues of common carp (Cyprinus carpio) and rainbow trout (Oncorhynchus mykiss) exposed to transport stress. In carp, the constitutive form (HSC70) was detected only in red skeletal muscle of both control and stressed animals. In the same species, the inducible form (HSP70) was evident in the epithelia of renal tubules, gills and skin of stressed animals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
4
13
0
Order By: Relevance
“… 47-54 In addition, studies conducted in other fish species showed the expression of HSP70 linked to the occurrence of transport stress. 55 , 56 As a preliminary consequence, we can suggest that all the experimentally applied temperatures, not accompanied by a HSP70 expression, are to be considered within the physiological range for this species and for the studied stages.…”
Section: Discussionmentioning
confidence: 84%
“… 47-54 In addition, studies conducted in other fish species showed the expression of HSP70 linked to the occurrence of transport stress. 55 , 56 As a preliminary consequence, we can suggest that all the experimentally applied temperatures, not accompanied by a HSP70 expression, are to be considered within the physiological range for this species and for the studied stages.…”
Section: Discussionmentioning
confidence: 84%
“…HSPs play a role in protein misfolding correction and defensive immature polypeptides from assemblage under stress, as well as, protecting the cells from proteotoxicity repaired protein impairment and facilitating the cell growth until conditions are improved (Barnes et al, 2002 ; Wang et al, 2003 ; Multhoff, 2007 ). Likewise, Poltronieri et al ( 2008 ) found the increasing of HSP70 in several tissues of common carp ( Cyprinus carpio ) and rainbow trout ( Oncorhynchus mykiss ) exposed to transport stress. HSC70 is one of the constitutive members in HSP70 family, playing a significant chaperoning role in unstressed cells (Yamashita et al, 2004 ).…”
Section: Discussionmentioning
confidence: 91%
“…). In fish and mammals, heat shock protein (HSP) acts at the cellular level as a general stress response system in addition to the HPI axis (Cara, Aluru, Moyano & Vijayan ; Poltronieri, Negrato, Bertotto, Majolini, Simontacchi & Radaelli ). Heat shock protein family proteins play critical roles in the stress response of aquatic organisms (Piccinetti et al .…”
Section: Introductionmentioning
confidence: 99%
“…Cortisol is usually lowest at hatching, it increases slightly at first feeding, and continues to rise through the flexion stage and all subsequent stages, indicating that in most fish larvae it begins to be produced around the shift from endogenous to exogenous feeding (Perez-Dominguez, Tagawa, Seikai, Hirai, Takahashi & Tanaka 1999;Szisch, Papandroulakis, Fanouraki & Pavlidis 2005;Bertotto et al 2011). In fish and mammals, heat shock protein (HSP) acts at the cellular level as a general stress response system in addition to the HPI axis (Cara, Aluru, Moyano & Vijayan 2005;Poltronieri, Negrato, Bertotto, Majolini, Simontacchi & Radaelli 2008). Heat shock protein family proteins play critical roles in the stress response of aquatic organisms (Piccinetti et al 2012), but their ontogeny in post-hatching development remains to be established for most species, including ballan wrasse.…”
Section: Introductionmentioning
confidence: 99%